Soluble silicon (Si) as potential treatment of post harvest decay caused by Fusarium proliferatum - Nur Azlin A.,; Shuhada Z.,; Najwa J.,; Jin, Xiaolei; Siti Nordahliawate M. Sidique, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Fusarium proliferatum is one of the common causal agents for pre-harvest and post-harvest diseases of plants. This study examined the effectiveness of applying soluble silicon as an alternative treatment in controlling post-harvest disease. In vitro assay was performed by applying poison plate technique with three different Si concentrations; 1.5% Si (v/v), 2.5% Si (v/v) and 3.5% Si (v/v) whereas for in vivo assay, F. proliferatum was inoculated into mature and healthy produce. The cucumber and aubergine were selected for in vivo assay and stored at 27-28°C for 8 days after treatment to assess disease severity. Results showed that Si significantly inhibited mycelial growth of F. proliferatum in vitro and the 3.5% (v/v) of Si was more effective than 1.5% (v/v) and 2.5 (v/v) as it showed a greater percent inhibition of radial growth. Therefore, 3.5% Si (v/v) was chosen for in vivo assay. The soluble Si demonstrated a lower disease severity on both, cucumber and aubergine. However, F. proliferatum is less severe on cucumber (15% decaying) than aubergine (33% decaying). This suggests that the Si may inhibit the germination of fungal spores and the elongation of their germ tubes. There is a potential role of soluble silicon as a decay-control product and could help reduce wastage especially fruit in storage.